Status of red palm weevil damage in East Godavari district and strategies for control with ecofriendly methods - Sujatha, A.; Chalam, M.S.V.; Arulraj, S. (Journal of Plantation Crops, 2009)
A roving survey conducted during 2003 and 2004 to assess the damage level of red palm weevil in four major coconut growing districts of Andhra Pradesh i.e., East Godavari, West Godavari, Visakhapatnam and Srikakulam revealed East Godavari district as the hot spot area for the pest. Root feeding with Azadirachtin 5 % WSC was found effective in preventing further damage and spread of red palm weevil in the garden. The study confirmed that azadirachtin 5 % WSC can be a suitable botanical substitute for monocrotophos 36 % SL through root feeding against this pest. Aggregation pheromone lures deployed in various infested gardens decreased the damage levels of red palm weevil. A sustainable IPM for red palm weevil was suggested with ecofriendly components.